2020
DOI: 10.1002/joc.6737
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the performance of drought indicators in Australia from 1900 to 2018

Abstract: Drought is a complex natural hazard caused by a combination of atmospheric and hydrological processes. Many different drought indicators have been developed, with each indicator varying in its calculation and its focus on different types of drought (e.g., meteorological, agricultural, hydrological, socioeconomic , etc.). Despite this, drought still remains poorly understood. The objective of this study is to compare different drought indicators and highlight their similarities, differences, strengths and weakn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Drought can be defined and measured in many different ways ( 24 , 25 ). More than 100 indices are used to measure the existence of drought, its duration, and severity for specific areas in given time periods ( 26 ). Each drought indicator can also be calculated based on different periods (windows) of antecedent environmental and climate conditions (e.g., rainfall, soil moisture, ground water conditions over the preceding 3, 6, 12, or 60 months) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought can be defined and measured in many different ways ( 24 , 25 ). More than 100 indices are used to measure the existence of drought, its duration, and severity for specific areas in given time periods ( 26 ). Each drought indicator can also be calculated based on different periods (windows) of antecedent environmental and climate conditions (e.g., rainfall, soil moisture, ground water conditions over the preceding 3, 6, 12, or 60 months) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, studies using a specific aspect of mental health such as suicide (5,11,12), or life satisfaction (13), have found that drought (using environmental measurement) is linearly related to poor mental health outcomes. O' Brien et al (14) examined drought characteristics as exploratory variables of mental health outcomes and showed that a long drought (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) months in an unbroken dry period) is associated with increased psychological distress (measured by the .…”
Section: Introductionmentioning
confidence: 99%
“…Start and end refer to the first and last month of a drought, where drought is declared if the rainfall total in the previous 3-or 6-month period is in the bottom 25% of historical rainfall totals for that corresponding 3-or 6-month period Gibson et al 2020;Askarimarnani et al 2021). This makes it difficult to plan drought emergency relief interventions as evident in 2015-2016 in Fiji-without data the Food Security and Agriculture Cluster found it hard to know where intense agricultural drought was occurring and how many farmers were affected.…”
Section: %mentioning
confidence: 99%
“…Furthermore, the available observations are usually not sufficient to capture the true spatiotemporal variability of drought (e.g. Easterling 2013;Gibson et al 2020;Askarimarnani et al 2021) or the lag of months to years between rainfall deficits (i.e. meteorological drought) and the progressive depletion of surface, soil and groundwater stores (i.e.…”
Section: Knowledge Gaps and Recommendations For Future Workmentioning
confidence: 99%
“…Further, many of the previous studies only analysed the occurrence and concurrence of droughts and heatwaves after the 1940s (e.g. Mueller and Seneviratne, 2012;Hajani et al, 2017;Sharma and Mujumdar, 2017;Sarhadi et al, 2018;Rashid and Beecham, 2019;Trancoso et al, 2020), which, for example, overlooks the widespread droughts in Australia between the 1890s and 1940s (Askarimarnani et al, 2020). The analysis covered 1889-2019 and provided a new perspective into the temporal trends of CHD events across the country.…”
Section: Introductionmentioning
confidence: 99%